1995
DOI: 10.1128/iai.63.5.1800-1805.1995
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa exoenzyme S induces proliferation of human T lymphocytes

Abstract: Pseudomonas aeruginosa is a gram-negative bacterium that is responsible for devastating acute and chronic infections, which include bronchiectasis in cystic fibrosis, nosocomial pneumonia, and infection of burn wounds. Previous studies have demonstrated that these patients have impaired host responses, including cell-mediated immune responses, which are important in anti-Pseudomonas host defense. The P. aeruginosa exoproduct, exoenzyme S, has a number of characteristics which suggest that it might be important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 37 publications
3
10
0
1
Order By: Relevance
“…Finally, T-cell proliferation to exoenzyme S is not blocked by an anti-DR antibody as is the case with other well-characterized mitogens (39). Previous data which show that greater than 95% of tested adults proliferated to exoenzyme S in vitro are also consistent with a T-cell mitogen (32).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Finally, T-cell proliferation to exoenzyme S is not blocked by an anti-DR antibody as is the case with other well-characterized mitogens (39). Previous data which show that greater than 95% of tested adults proliferated to exoenzyme S in vitro are also consistent with a T-cell mitogen (32).…”
Section: Discussionsupporting
confidence: 69%
“…Research has therefore focused on identifying antigenic determinants of the microorganism that are recognized by T cells of normal healthy adults. We have recently reported that a purified preparation of exoenzyme S induces T cells to proliferate in over 95% of adults (32). The high frequency of adult responders suggests that exoenzyme S may be stimulating T cells as a mitogen or superantigen.…”
mentioning
confidence: 99%
“…A single nucleotide polymorphism within recipient TLR4 that is associated with decreased sensitivity of TLR4 was found to be protective against ACR [69]. Pseudomonas itself can preferentially cause CD4 T cell activation and proliferation, via exoenzymes such as exotoxin-A, though such exoenzymes may require preprocessing by an appropriate antigen presenting cell [70,71]. Pseudomonas causes an accumulation of lymphocytes in the perivascular space and stimulates T cells to produce both IFN-γ and IL-1, both of which have been associated with allograft rejection.…”
Section: Because Of the Tremendous Infectious Burden Imposed By Bothmentioning
confidence: 99%
“…After appropriate consent (approved by the Conjoint Health Research Ethics Board at the University of Calgary), human PBMCs were isolated via Ficol-Hypaque separation from blood of healthy donors as reported previously [44].…”
Section: Antibodies and Antiserummentioning
confidence: 99%